Lexico-semantic group of the verb “to break” in modern english - Umurova Xushvaxt Xakimovna (Indonesian Journal of Innovation Studies, 2019)
This article is dedicated to the lexico-semantic variants of the verb “to break” in modern English. Moreover, the lexico-semantic group of the verb “to break” in modern English was investigated in different ways. The conclusions of the research were directed to make better analyses for the future points.